The Influence of Tax Knowledge, Activeness of Village Parties, and Tax Sanctions on Taxpayers' Non-Compliance in Paying Land and Building Tax - Hastin Tri Utami; Ananda Nur Kholifah (Mabsya: Jurnal Manajemen Bisnis Syariah, 2023)
Taxpayer non-compliance is an action that referes to a situation where a taxpayer has not been able to fulfil all of his tax obligations. Evaluation data on PBB tax revenue in Ajibarang District shows that in Tipar Kidul Village from 2019-2021 there has been a reduction in taxes in the realization of the principal tax assessments. This is what causes tax non-compliance in Tipar Kidul village.Im this study, researchers analyzed the influence of tax knowladge, the activeness of village partise and tax sactions on taxpayer non-compliance in paying land and building taxes in Tipar Kidul Villafe, Ajibarang District, Banyumas regency. The purpose of this study is to determine the effect of tax knowladge, activeness of village partise and tax sactions on taxpayer non-compliance in paying land and building taxes. The method used in this research is quantitative with probability sampling technique, namely cluster random sampling and non-probability sampling, namely purposive sampling with a total sampel of 380. The result of this study indicate that : 1) tax knowledge has noo negative effect on taxpayer non-compliance in paying land and building taxes. 2) the activeness of village partise has a negative effect on taxpayer non-compliance in paying land and building taxes. 3) tax sanctions have a positive effect on taxpayer non-compliance in paying land and building taxes. 4) simultaneously all the independent variabel in this study have a significant positive effect on taxpayer non-compliance in paying land and building taxes.